Hubungan Dukungan Keluarga Dengan Kemandirian Lansia Dalam Pemenuhan Activities Daily Living (ADL) di Kelurahan Bailang Lingkungan V Kecamatan Bunaken Kota Manado - Nurlela Hi. Baco; I Made Rantiasa (Jurnal Medika Nusantara, 2023)
Elderly is a phase of life that will be experienced by every human as well as aging. The aging process causes various physical, biological, mental and socio- economic problems. This process as a result of a degenerative (aging) process. Therefore, non-communicable diseases often occur in the elderly. Non-communicable diseases that are often experienced by the elderly include hypertension, stroke, heart disease, diabetes mellitus and joint inflammation or rheumatism. The purpose of this study was to determine the relationship between family support and independency of elderly in fulfilling ADL in Bailang Village, Area 5, Bunaken District, Manado City.This study used a descriptive analytic design with a cross sectional approach. The sampling technique in this study is purposive sampling with number of samples in this study were 33 respondents. The research instrument for data collection used in this study is a questionnaire. Furthermore, the data that has been collected is processed using computer program SPSS version 21 and analysed using statistical tests Chi-square with a significance level (?) 0.005.The study results showed that 18 (54.5%) respondents had good family support and 15 (45.5%) respondents had lack family support. Chi-square test obtained value = 0.003 (<0.005), That means there is a significant relationship between family support and the independency of the elderly in fulfilling Activity daily Living (ADL).The conclusion of this study is there is a relationship between family support and the level of independency of the elderly in fulfilling ADL in Bailang Village, Area V, Bunaken District, Manado City. The suggestions from this study are hopefully the family can understand the problems of the elderly, give support, and appreciation if elderly are able to do the activities independently.